Penerapan Model Examples Non Examples untuk Meningkatkan Hasil Belajar IPS Tema 7 Indahnya Keragaman di Negeriku Kelas IV SDN Sambeng Wetan - Dewi, Fera Puspita (Jurnal Kualita Pendidikan, 2024)
Social studies aims to develop knowledge, understanding of concepts that can improve students' ability to work together, tolerate, and improve their learning outcomes. Based on the results of observations, interviews and document data conducted by researchers with the collaboration team, there are problems in class IV SDN Sambeng Wetan, namely low social studies learning outcomes. To improve these problems, classroom action research was conducted by applying the Examples Non Examples model. The formulation of the research problem is "Can the application of the Examples Non Examples model improve the learning outcomes of Social Studies Theme 7 The Beauty of Diversity in My Country of Class IV SDN Sambeng Wetan?". The research was carried out in two cycles. Each cycle consists of planning, implementation, observation, reflection. Data collection techniques used tests and non-tests. Data analysis used quantitative and qualitative analysis. The results of the study showed that the average score of teacher activity in cycle I was 2.82 (good), cycle II was 3.70 (very good). The average score of student activity in cycle I was 2.90 (good), cycle II was 3.55 (very good). The percentage of completion of cognitive learning outcomes of students in cycle I is 68.42%, cycle II is 89.47% (KKM 67). The affective learning outcomes of students in cycle I are 3.03 (Good), cycle II is 3.30 (Very Good). The psychomotor learning outcomes of students in cycle I are 2.87 (Good), cycle II is 3.33 (Very Good).